Interpolations of class, “race”, and politics - Mylonas Yiannis; Noutsou Matina (Nordicom Review)
This article focuses on the ways in which the Danish liberal mainstream press covered events related to the so-called Greek crisis. In particular, we examine the coverage of the different Greek national elections that took place during the Greek crisis years (2010–2019) by Jyllands-Posten (JP), a popular Danish daily newspaper. Qualitative content analysis is deployed to study a corpus of 70 news and editorial articles published by JP on the aforementioned topic. Our analysis highlights the existence of three main interrelated themes in JP's constructions of the Greek elections: a moralist, a culturalist, and a technocratic/anti-leftist theme. These themes are theorised through the use of relevant theory on class cultures and politics today.